Coercive geographies (Leiden ; Boston)
xiii, 230 sayfa
Keywords: “Responding to the deteriorating situation of migrants today and the complex assemblages of the geographies they navigate, Coercive Geographies examines historical and contemporary forms of coercion and constraint exercised by a wide range of actors in diverse settings. It links the question of spatial confines to that of labor. This fraught nexus of mobility and work seems self-evidently relevant to explore. Coercive Geographies is our attempt to bring together space, precarity, labor coercion and mobility in an analytical lens. Precarity emerges in particular geographical and historical contexts, which are decisive for how it is shaped. The book analyzes coercive geographies as localized and spatialized intersections between labor regulations and migration policies, which become detrimental to existing mobility frameworks. Contributors include: Irina Aguiari, Abdulkadir Osman Farah, Leandros Fischer, Konstantinos Floros, Johan Heinsen, Martin Bak Jørgensen, Martin Ottovay Jørgensen, Apostolos Kapsalis, Karin Krifors, Sven Van Melkebeke, Susi Meret, and Vasileios Spyridon Vlassis“ --